Race, Rights, and Justice - Angelo Corlett, J. (Law and Philosophy Library, 2009)
Race, Rights, and Justice explores questions of the nature of law and constitutional interpretation, international law and global justice, and the nature, function, and importance of rights each from a perspective that takes seriously the realities of race and racism. After a critical assessment of various contemporary theories of law is provided, a new theory of legal interpretation is set forth and defended. The respective words of Immanuel Kant and H. L. A. Hart on the possibility and desirability of international law are carefully explicated. Following this, Race, Rights, and Justice defends John Rawls' Law of Peoples from the cosmopolitan liberal critique of it. The nature and importance of rights, both individual and collective, are clarified while correcting some political philosophies that have propagated confused rhetoric about rights. And the collective right to humanitarian intervention is investigated philosophically in terms of the recent problems in Colombia, with surprisingly original results. While the methodology of this book is thoroughly analytical, philosophically speaking, some of the conclusions drawn are substantially original, infusing the facts of race and racism into mainstream matters of philosophy of law. "In this collection of essays, J. Angelo Corlett continues his important work of bringing the perspective of indigenous peoples, and more generally of race, into mainstream philosophical debates about justice and rights. Corlett's book also has very valuable insights into the nature of international law that will greatly enrich our contemporary debates." Larry May, Washington University in St. Louis, USA "Angelo Corlett is a prolific writer whose work is invariably stimulating, provocative, and insightful. Race, Rights, and Justice is an important addition to the oeuvre. Corlett is not afraid to tackle big problems, and big names. See, for example, his scathing criticisms of Bork and Scalia on constitutional interpretation." Burleigh T. Wilkins, University of California, Santa Barbara, USA